2015
DOI: 10.1063/1.4929429
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of defect-induced abnormal body current in fin field-effect-transistors

Abstract: This letter investigates the mechanism of abnormal body current at the linear region in n-channel high-k/metal gate stack fin field effect transistors. Unlike body current, which is generated by impact ionization at high drain voltages, abnormal body current was found to increase with decreasing drain voltages. Notably, the unusual body leakage only occurs in three-dimensional structure devices. Based on measurements under different operation conditions, the abnormal body current can be attributed to fin surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…145) ) As seen in the case of incident species with lighter masses, the number of generated defects increases considerably with an increase in the energy of incident species. The presence of defects in a finFET was discussed, 146) although the detailed mechanisms has not been clarified at this stage in terms of stochastic straggling. Recently, this predicted phenomenon was experimentally verified.…”
Section: Ppd Range Theory and Device Performance Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…145) ) As seen in the case of incident species with lighter masses, the number of generated defects increases considerably with an increase in the energy of incident species. The presence of defects in a finFET was discussed, 146) although the detailed mechanisms has not been clarified at this stage in terms of stochastic straggling. Recently, this predicted phenomenon was experimentally verified.…”
Section: Ppd Range Theory and Device Performance Degradationmentioning
confidence: 99%
“…Then, the resultant density of defects in the distribution tail or in the 3D structure should be quantified. 146) Sato et al revealed 147) the PPD stochastic mechanisms using a specified device structure. 147) As shown in Fig.…”
Section: Electrical Characterizationmentioning
confidence: 99%